2018
DOI: 10.1038/s41419-018-0876-3
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 derived from tumor-associated macrophages promotes breast cancer metastasis via activating NF-κB/SOX4 signaling

Abstract: Tumor-associated macrophages (TAMs) have been implicated in the promotion of breast cancer growth and metastasis, and multiple TAM-secreted cytokines have been identified associating with poor clinical outcomes. However, the therapeutic targets existing in the loop between TAMs and cancer cells are still required for further investigation. Here in, cytokine array validated that C-X-C motif chemokine ligand 1 (CXCL1) is the most abundant chemokine secreted by TAMs, and CXCL1 can promote breast cancer migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
167
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(190 citation statements)
references
References 46 publications
7
167
0
Order By: Relevance
“…However, our previous findings demonstrated that CXCL1 acts as the highest chemokine secreted by TAMs isolated from breast cancer [16,41]. Moreover, CXCL1 silencing in TAMs was found to inhibit breast cancer growth and lung metastasis via inhibiting NF-κB/SOX4 signaling in both murine and human models [42]. Similar results were also observed in other malignancies.…”
Section: Discussionsupporting
confidence: 59%
“…However, our previous findings demonstrated that CXCL1 acts as the highest chemokine secreted by TAMs isolated from breast cancer [16,41]. Moreover, CXCL1 silencing in TAMs was found to inhibit breast cancer growth and lung metastasis via inhibiting NF-κB/SOX4 signaling in both murine and human models [42]. Similar results were also observed in other malignancies.…”
Section: Discussionsupporting
confidence: 59%
“…However, the role of CXCL1 in prostate-specific PTEN KO-induced PCa progression has been poorly investigated. 41 Also, targeting IL-6 and TIMP4 interactions with a CXCL1 monoclonal antibody offers a novel strategy to F I G U R E 7 Validation of the mRNA changes observed for selected genes and their regulation by PTEN loss. 39 Increased CXCL1 protein levels were present in high-grade malignancies, in which it was associated with higher-grade prostate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…40 Increasing evidence shows that TAMs/ CXCL1 promotes breast cancer metastasis via NF-κB/ SOX4 activation, and CXCL1-based therapy might become a novel strategy for breast cancer metastasis prevention. 41 Also, targeting IL-6 and TIMP4 interactions with a CXCL1 monoclonal antibody offers a novel strategy to therapeutically manage prostate and bladder cancers. 42 A recent study showed that obese patients with PCa have increased epithelial CXCL1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mining of our RNAseq dataset revealed expression changes in EMT-related genes upon CFIm25 depletion, especially in the KRAS mutant cells, including increased TGF-b2 expression, reduced Occludin, and significant upregulation of multiple EMTassociated chemokines ( Supplementary Fig. 7b), providing more evidence that CFIm25 regulates EMT [50][51][52] .…”
Section: Cfim25 Regulates 3'utr Shortening Of Conserved Genesmentioning
confidence: 92%